PENGARUH TINGKAT KEMAHALAN HARGA SAHAM, KINERJA KEUANGAN PERUSAHAAN DAN LIKUIDITAS PERDAGANGAN SAHAM TERHADAP KEPUTUSAN PERUSAHAAN MELAKUKAN STOCK SPLIT - Jurica Lucyanda; Ditya Anggriawan (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
This study aims to examine the effect of the over price d stock prices, the company's financial performance and liquidity of stock trading on the company's decision to doa stock split and its impact on corporate value. In this study the level of over price dstock prices measured by the Price Earnings Ratio and Price to Book Value,the company's financial performance is measured by Return on Assets and Earnings Per Share,liquidity of stock trading volume is measured by the Trading Activity and firm value will be measured by the earnings and Tobin's q. Analysis tools will be used in this study are the logistic regression and two independent sample t-test. This study used a sample a mounted to 31 go public companies that do the stock-split and 31 go public companies who do not do stock splits during the period 2003-2009. Based on the results of testing, found that the level of over price dstock prices as measured by the ratio of Price to Book Value affect the company's decision to do stock splits and stock trading liquidity which measured by Trading Volume Activity also affects the company's decision to doa stock split. But this study failed to show any differences between the values of the companies that do the stock-split with the companies that do not do stock splits. Key words: price earnings ratio, price to book value,earnings per share,return on assets, trading volume activity, earnings, tobins'q